Effect of mesh refinement on vertical and lateral velocity profiles of the wake flow behind a spire based on computational fluid dynamic (CFD) - Muhammad Arifuddin, Fitriady; Nurizzatul Atikha, Rahmat; Ahmad Faiz, Mohammad; Sheikh Ahmad, Zaki (UTEM, 2023)
The application of CFD to simulate the phenomenon based on a wind tunnel experiment has been widely studied. A large number of cells may produce accurate results but requires a high computational load. In this study, the effect of mesh refinement on the vertical and lateral velocity profiles of the wake flow behind a single spire is discussed. Three different mesh refinement levels, i.e. coarse, medium and fine, each with 9 million, 12.7 million, and 16.9 million cells, respectively, were applied to the computational domain. The standard k-ε model was used as turbulence model. The variable mesh was generated by using blockMesh and snappyHexMesh features in the OpenFoam® software. Based on the results, it can be stated that a slight difference between each cases, which reduced as the distance increase in both vertical, and sreamwise direction, was observed. However, there is a significant difference in the time needed to complete the iteration for each case whereby the shortest duration was performed by the coarse case. Hence, it is more feasible to adopt the coarse case to simulate the wake flow behind a single spire.